Faktor-Faktor yang Mempengaruhi Minat Karier Mahasiswa Akuntansi di Industri Perbankan - Kholida Alfi Eka Damayanti; Fauzan Fauzan (Journal of Accounting, Management, and Economics Research (JAMER), 2026)
This study aims to analyze the factors influencing accounting students’ interest in choosing a career as a banker in Sukoharjo Regency. The research examines the influence of salary, social values, work environment, and parental influence on students’ career choices in the banking sector. This study was motivated by the increasing interest of accounting students in banking careers due to career stability, professional reputation, and attractive financial rewards offered by the banking industry. This research employed a quantitative approach using primary data collected through questionnaires distributed to 99 accounting students in Sukoharjo Regency. The data were analyzed using multiple linear regression analysis with the assistance of SPSS software. The results indicate that salary has a positive and significant effect on accounting students’ interest in pursuing a banking career, while social values and parental influence have a positive but insignificant effect. Meanwhile, the work environment has a negative and insignificant effect on career choice. The findings contribute to understanding accounting students’ career preferences and provide managerial implications for banking institutions and universities in developing recruitment strategies and career guidance programs for prospective graduates.